Social Media Use and Attitudes toward AI: The Mediating Roles of Perceived AI Fairness and Threat - Wenbo Li; Xia Zheng (Human Behavior and Emerging Technologies)
This study investigates the association between social media use and attitudes toward AI technologies. A nationally representative two-wave longitudinal survey (N=5110) examined the mediating roles of perceived AI fairness and threat concerning three AI technologies: algorithms, facial recognition technology, and driverless passenger vehicles. Hypotheses were derived from media effect theories and the heuristic and systematic model of human-AI adoption. The results showed that social media use predicted more positive attitudes toward the three AI technologies indirectly through increased perceived AI fairness and reduced perceived AI threat. The findings contribute to our understanding of social media effects on attitudes toward AI and the underlying psychological mechanisms, providing valuable theoretical insights and practical implications.